Studi Perbandingan Antara Maserasi dan Accelerated Solvent Extraction (ASE) terhadap Hasil Ekstrak Daun Kalangkala (Litsea angulata) - Akbar, Nabila Hadiah; Buih , Putri Helena Junjung; Muslimawati , Khoirunnisa; Putra , Aditya Maulana Perdana; Amalia , Adhindha; Putri , Dhea Juliana (Journal of Pharmaceutical and Sciences, 2026)
Kalangkala (Litsea angulata) is an endemic plant of Kalimantan that has long been used in local traditional medicine to manage various health conditions. Phytochemical reports indicate that Kalangkala contains diverse secondary metabolites, including phenolics, flavonoids, alkaloids, tannins, saponins, terpenoids, steroids, and carotenoids. Therefore, selecting an appropriate extraction method is essential to maximize metabolite recovery while minimizing degradation. This experimental study compared the extraction yield of Kalangkala leaf extract obtained using maceration and ASE (Accelerated Solvent Extraction) methods. Each method was performed in three replicates and the percentage yield was calculated. Maceration produced yields of 2.10-2.18%, whereas ASE produced higher yields of 13.25-14.01%. the mean yield of maceration was 2.14 ± 0.04% (95% Cl: 2.04-2.24), while ASE achieved 13.64 ± 0.38% (95%Cl: 12.69-14.58). A two-tailed Welch’s t-test confirmed a statistically significant difference between methods (p = 0.00032), with a mean difference of 11.49% (95% Cl: 10.56-12.42). In conclusion, ASE provided a higher extraction yield than maceration under the conditions evaluated in this study.